Issues and Challenges in Implementing Outcome Based Education in Engineering Education - Rajaee, N.; Junaidi, E.; Taib, S.N.L.; Salleh, S.F.; Munot, M.A. (International Journal for Innovation Education and Research, 2013)
In recent years, the implementation of outcome based education (OBE) has been much emphasized in developed and developing nations which led to becoming the focal point for educational reforms. In outcome based education, students are responsible for their own learning and the assessment of learning are based on the outcomes instead of the contents being taught. However, much criticism against the OBE has also been presented in various papers regarding the actual implementation of OBE. In this paper, we discussed the issues and challenges of implementing an outcome based education in engineering education particularly in Faculty of Engineering, UNIMAS, Malaysia.